The Impact of Collaborative Gameplay in Mobile Legends on Developing Strategic Thinking and Team Leadership Skills in Gen Z - dilla vitriani, shalsa; Bintani, Ralda Ayu; Widhia, Nina agnes; Setiawan putri, Nindan karang; Ayunda Pratiwi, Mirza; Anggi Fani, Lastri (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
Mobile Legends has become an incredibly popular game among Generation Z. However, the positive impact of this game on skill development, particularly in leadership, remains a question. This study aims to examine how the experience of playing Mobile Legends can influence leadership skills and strategic thinking in Generation Z. Given that the game requires teamwork, tactical thinking, and quick decision-making, this research employs a qualitative method through in-depth interviews with ten active Mobile Legends players selected via purposive sampling. Through this approach, various perspectives can be revealed regarding their gaming experiences. The results of the study indicate that Mobile Legends has the potential to serve as a medium for developing leadership skills, especially in the context of teamwork and decision-making in rapidly changing situations. However, this positive impact is only evident in players who consciously apply these skills in real life, rather than just within the game. Therefore, the findings of this study are expected to provide new insights into how online games can help develop important skills for Generation Z, particularly in leadership and strategy. To ensure a lasting positive impact, this game needs to be played wisely and with a clear purpose. This research concludes that, with the right approach, Mobile Legends can significantly support the development of leadership skills and strategic thinking among Generation Z.